A rare case of triplet heterotopic pregnancy with a live intrauterine and bilateral tubal ectopic - Agarwal, Poonam; Goyal, Kiran Raman; Agarwal, Apurv (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Heterotopic pregnancy (HP) is a condition characterized by the coexistence of an ectopic pregnancy (EP) with a viable intrauterine pregnancy (IUP). The occurrence of a triplet heterotopic pregnancy is an exceptionally rare medical condition. Hence, timely diagnosis and management are challenging, but essential to prevent mortality. Authors report the case of a young woman who presented with a heterotopic triplet pregnancy, after in-vitro fertilization (IVF), at 12 weeks of gestation. She had been misdiagnosed as a case of severe ovarian hyperstimulation syndrome but had a ruptured tubal ectopic on the right side and an unruptured ectopic on the left side. Both the ectopics were managed by performing an emergency laparotomy with bilateral salpingectomy. The live intrauterine pregnancy was continued till term with the delivery of a healthy baby. High clinical suspicion and timely treatment can preserve the intrauterine gestation thus, ensuring a successful outcome.